DEVELOPMENT OF MATHEMATICS PICTURE STORY BOOK ON FRACTION MATERIAL FOR GRADE IV ELEMENTARY SCHOOL STUDENTS - Mananggel, Marlin Blandy; Ramadhani, Widya Putri; Makaruku, Yulian Hani (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2024)
Mathematics picture story books are learning media that can help students learn mathematics content both independently or through active interaction in the classroom. This study aims to develop learning media for mathematics picture story books on Fraction material and determine its feasibility for grade IV elementary school students. This research is an R&D research with ADDIE model which consists of stages 1) analyze, 2) design, 3) development, 4) implementation, and 5) evaluate. The subjects in this study were 40 fourth grade students at SD Negeri 318 Maluku Tengah, SD Negeri 254 Maluku Tengah and SD Kristen Tiouw. Before being tested, this book was first validated by material experts and media experts. This research produces a product in the form of illustrated storybooks as a medium for learning mathematics on Fraction material. Based on the assessment of material experts get a validity percentage of 89% category